Exact traveling wave solutions of (2+1)-dimensional extended Calogero-Bogoyavlenskii-Schiff equation using extended trial equation method and modified auxiliary equation method - Akram, Ghazala; Sadaf, Maasoomah; Arshed, Saima; Latif, Rimsha; İnç, Mustafa; Alzaidi, Ahmed S. M. (Springer, 2024)
The (2+1)-dimensional extended Calogero-Bogoyavlenskii-Schiff equation appears in the mathematical description of physical phenomena in plasma physics, fluid dynamics and nonlinear optics. In this article, extended trial and modified auxiliary equation methods are utilized to observe the dynamical structures exhibiting the solitary wave behavior of the considered model. The traveling wave hypothesis is employed to extract explicit closed-form solution expressions. The presented methods show reliability and robust computational capabilities to investigate solitary waves. In order to investigate the physical behavior of these solutions, 3D, 2D and density plots are drawn for different values of parameters. The graphical observations depict kink soliton, dark-bright singular soliton and periodic wave solutions. The comparison of the outcomes of the proposed results with those obtained using prior techniques is made to confirm the usefulness of the proposed techniques. The presented study will be helpful to explain the wave propagation in many problems of plasma physics and fluid dynamics. Moreover, the reported solutions may help to understand optical wave transmission and aid in the development of optical devices. The results given in this study will contribute in the understanding of the behavior of waves in the higher-dimensional governing models.
Keywords: (2+1)-Dimensional extended Calogero-Bogoyavlenskii-Schiff equation; Extended trial equation method; Modified auxiliary equation method; Traveling wave solutions